دور نشر ثقافة الجودة في تحقيق التنمية السياحية بالجزائر - يحياوي, الهام (Université de M'sila, 2012)
تعد ثقافة الجودة إحدى الركائز الأساسية في تحقيق التنمية السياحية فضلا عن دورها في تعزيز القيم والمعتقدات والسلوكيات لدى الأفراد من أجل التوجه نحو تطبيق إدارة الجودة الشاملة. يحاول البحث تقديم إطار نظري حول إمكانية نشر ثقافة الجودة في تحقيق التنمية السياحية بالجزائر لمواجهة التحديات التنافسية التي تواجهها في السوق ووصولها إلى النجاح والتميز.
Quality culture is considered one of the fundamental bases to contribute tourism development, in addition to its role to enhance the bvalues, beliefs and behaviors for employees in organizations in order to apply total quality management. This research is an attempt to introduce a theoretical and applicable frame about the ability of quality culture deployment to contribute tourism development in Algeria which face dit in the market and reach to the success and differentiation